Sistem Rujukan RS Terdekat Berbasis Model-Driven DSS (A*) di Kota Bandung - Salma Rahayu; Irman Hariman (Universitas Kebangsaan Republik Indonesia, 2025)
This study aims to develop a model-driven Decision Support System (DSS) designed to determine hospital referrals in Bandung City by considering the nearest distance as the primary criterion. The motivation for this research is the growing demand for efficient referral mechanisms that can assist both patients and healthcare providers in making objective, fast, and location-based decisions. The proposed system integrates Global Positioning System (GPS) coordinates as user input and applies the A search algorithm to calculate the most optimal route between the user’s position and the selected hospital. The dataset consists of a graph-based map of Bandung nodes combined with a hospital database containing detailed information on available polyclinics. The system generates recommendation tables that present hospital names, types, addresses, distances, statuses, and classes, allowing users to compare referral options more comprehensively. Experimental evaluation shows that the A* algorithm consistently produces valid distance calculations compared with manual measurements, confirming the reliability of the system in processing spatial data and generating accurate recommendations. Therefore, the model-driven DSS proposed in this study provides a practical and effective solution to improve the efficiency of medical decision-making processes in Bandung City, particularly in referral determination.